You Say You Want a REV Solution: Considering New York’s Marquee Energy Initiative as Climate Change Policy - Ratzkin, Andrew (Columbia Journal of Environmental Law, 2019)
This past fall, in a pair of remarkable speeches at New York University and Columbia University, Governor Cuomo issued forceful, groundbreaking statements and demonstrated real leadership on climate change. He bluntly articulated the problem, and asserted its reality in direct, unequivocal terms. At the Columbia event, and elsewhere, New York’s Reforming the Energy Vision (“REV”) has been highlighted as the key pillar of the State’s climate change policy, the vehicle via which the State’s ambitious greenhouse gas (“GHG”) emissions reduction goals—forty percent reduction from 1990 levels by 2030, eighty percent reduction by 2050—would be achieved. This Article considers the REV from the standpoint of whether this initiative is likely to deliver on this promise. The New York State Public Service Commission (the “Commission”) has identified reduction of carbon emissions as one of six policy objectives associated with the REV.5 Yet, climate goals, to the extent identified in the current formulation of the REV, appear to be of second-order importance, unconnected to any binding commitments or actual, enforceable mechanism for achieving emissions reductions. This is cause for great concern, particularly considering the centrality of the REV in the State’s GHG emissions reduction strategy. The REV itself contains neither mandates nor a price signal adequate to significantly drive down combustion of fossil fuels in New York. The lack of such a price signal is particularly important considering the steep decline in the price of fossil fuels over the last twenty-four months. In fact, the REV has never been meaningfully assessed with respect to its impact on GHG emissions, and therefore little if any basis exists for crediting its emissions reduction claims. If addressing climate change is the fundamental policy goal—and the Governor’s recent statements should leave no doubt that it must be—then the REV, especially if it is suggested to be the primary means to achieve emissions goals, should squarely address GHG emissions as its primary objective. However, the REV does not read that way. Rather, the REV, as currently articulated, is directed primarily to issues of market reform, utility business model change, and decentralization. These are factors that certainly may facilitate the adoption of renewable energy, particularly distributed generation of renewable energy, but do not by themselves offer certainty about New York’s future energy mix or GHG emissions, as examined further below.